Hatching of Cryopreserved Human Blastocysts Obtained in IVF and ICSI Cycles - Shapovalova, Nataliia; Yurchuk, Taisiia; Pinyaev, Volodymyr; Petrushko, Maryna (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4):283